PELATIHAN PEMBUATAN JURNAL UMUM PERUSAHAAN JASA DI SEKOLAH DAERAH JAKARTA BARAT - Viriany; Wieleycia Terence; Erica; Melvin Vanwi Goenawan (Jurnal Serina Abdimas, 2026)
Merdeka Belajar Kampus Merdeka (MBKM) is a policy issued by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia to provide university students with opportunities to develop innovative and adaptive learning experiences in various regions. One of the selected MBKM activities is teaching assistance in educational units, particularly at the junior high school level. This teaching activity was conducted at SMP Katolik Ricci 1 for Grade VIII students, consisting of 23 learners. The program started in October and was held every Monday from 08:20 to 09:40 WIB. The learning process focused on introducing basic accounting materials, especially the preparation of general journals. The lessons began with theoretical explanations followed by practical exercises in journal preparation so that students could understand the logic before practicing independently. During the learning sessions, the instructor used simple and understandable language while creating a warm and interactive classroom atmosphere to encourage students to ask questions openly. Throughout the program, students demonstrated high enthusiasm toward the material being taught. Although several students initially experienced difficulties in understanding basic accounting concepts, they gradually improved through open discussions and guided practice. This activity is expected to motivate students to study more diligently and gain new knowledge in accounting. At the same time, the university student obtained valuable teaching experience and practical skills in education. Overall, the MBKM program contributes to developing insightful and critical-thinking future generations who are ready to face modern societal changes and educational challenges. Merdeka Belajar Kampus Merdeka adalah kebijakan baru yang dikeluarkan oleh Kementrian Pendidikan, Kebudayaan, Riset dan Teknologi Republik Indonesia yang bertujuan untuk memberikan kesempatan bagi mahasiswa untuk mengembangkan proses pembelajaran yang inovatif dan adaptif di berbagai daerah. Kegiatan MBKM yang dipilih adalah kegiatan asistensi mengajar di satuan pendidikan khususnya tingkat Sekolah Menengah Pertama (SMP). Kegiatan mengajar di satuan pendidikan dilaksanakan di SMP Katolik Ricci 1 dengan mengajar kelas VIII dengan murid yang berjumlah 23 orang yang mulai dari bulan Oktober yang diselenggarakan setiap hari Senin pukul 08.20-09.40 WIB. Proses pembelajaran dimulai dengan memaparkan materi seputar dasar-dasar akuntansi, seperti pembuatan jurnal umum. Materi yang dipaparkan diawali dengan penjelasan teori dan dilanjutkan pembuatan jurnal agar siswa/i memahami logika sebelum pembuatan jurnal umum. Selama proses berlangsung, pengajar semaksimal mungkin menjelaskan materi dengan bahasa yang mudah dimengerti dan menciptakan suasana yang hangat agar siswa/i tidak sungkan untuk bertanya. Selama proses pembelajaran, siswa/i menunjukkan antusiasme yang tinggi terkait materi dalam mengikuti materi. Walaupun ada beberapa siswa/i yang kesulitan dalam memahami konsep dasar, namun secara bertahap siswa/i tersebut mulai memahami karena pengajar membuka sarana untuk berdiskusi bersama. Melalui kegiatan ini, diharapkan siswa/i mendapatkan motivasi untuk giat belajar dan memperoleh pengetahuan baru di bidang akuntansi dan mahasiswa juga mendapatkan pengalaman baru dalam dunia pendidikan dengan mengajar ke sekolah-sekolah untuk memaparkan materi yang didapat selama masa perkuliahan. Program MBKM ini menjadi kesempatan berharga untuk menciptakan generasi bangsa yang berwawasan serta mampu berpikir kritis terhadap perkembangan zaman.